Experimental Research on the Mechanical Properties of Heated Granite after Rapid Cooling. (11th September 2021) - Han, Huifen; Peng, Junliang; Guo, Yintong; He, Qiuyun; Zhou, Jun; Gou, Xinghao
Abstract : Understanding the mechanical properties of the reservoir rock under different temperatures after rapid thermal cooling is necessary for safe and effective deep geoengineering applications, including deep mining projects, deep geological disposal of nuclear waste, and geothermal energy extraction. This paper is devoted to investigating the effect of rapid cooling on the mechanical behavior of the granite rock. At first, high-temperature heating was conducted. The 24 samples were divided into six groups and were heated at 100, 200, 300, 400, 500, and 600°C, and once they had reached the chosen temperature, they were immediately cooled with a cold water container, and the temperature of water in the pan was 25°C. After the thermal treatment, the samples were measured using ultrasonic wave velocities, and then they were deformed under uniaxial and triaxial compression tests. The P -wave velocity, damage characteristics, stress-strain curves, compressive strength, and Young's modulus of the samples were presented considering different thermal temperatures. The results confirmed that the P -wave velocities of the samples generally decrease with temperature. P -wave velocity can indirectly reflect the damage of the rock structure. These changes represent a negative exponential relationship between P -wave velocity and hold temperature following cooling. As the samples experienced greater temperatures, the peak strength and elastic characteristics also significantly reduced. This is mainly due to thermally induced damage in the form of both intergranular and intragranular cracks. The stress-strain response revealed that the failure mode can change from brittle to quasi-brittle fracturing following treatment at increasingly greater temperatures.